RELASI KEPALA DESA DAN BADAN PERWAKILAN DESA DALAM PEMANFAATAN DANA DESA DI KECAMATAN NAMLEA - Salma Yusuf; M Chairul Basrun Umanailo; Nirwana AR (Sosioglobal, 2020)
The Village fund is a government effort to support the development of the village through financing schemes that are regulated and implemented directly by the village government, the involvement of village institutions in the management of village funds into an institutional relationship that is able to Village Fund Management.  This research is a qualitative study aimed to describe the relationship of village government with village institutions in the planning and implementation of development based on the allocation of village funds obtained. The research site is focused on Namlea subdistrict with the consideration of density and heterogeneity of society. The number of informant that will be interviewed as many as 40 people taken in purposive. The analytical techniques used follow the concept given Miles and Huberman. The results showed that the relationship that awakened has a positive impact on the planning, implementation and supervision of the use of the village funds with the presence of the engagement, the sense of having and responsibility to the management Village funds are not merely the responsibility of the villagers but rather to be a responsibility with the parties involved.